Migration, trade and unemployment - Benedikt Heid; Mario Larch (Kiel Institute for the World Economy (IfW), 2011)
A source of anxiety of policy makers and the public in general is the detrimental impact of globalization and immigration on unemployment. The transitory restrictions for worker migration after the EU enlargements of 2004 and 2007 exemplify the supposed negative effect of immigration on labor markets. This paper aims to identify the effects of immigration alongside trade on unemployment taking into account the substitutability of worker and goods flows. We use data from 24 OECD countries over the period from 1997 to 2007 and employ instrumental variables fixed effects and dynamic panel estimators in order to account for unobserved heterogeneity as well as the potential endogeneity of migration flows and the high persistence of unemployment. We find a significant negative effect of immigration on unemployment on average.
Keywords: C23; C26; F15; F16; F22; 330; migration; unemployment; international trade; fixed effects instrumental variable panel estimators; dynamic panel estimators